Effect of a Fuzzy Neo-Based Temperature Control System on the Physicochemical Characteristics of Sweet Corn Yoghurt - Yunira, Eka Nur'azmi; Az-zahra, Nilandra Ayu; Pratama, Borneo Satria (Jurnal Keteknikan Pertanian Tropis dan Biosistem, 2026)
Milk can be utilized as a raw material in yoghurt production. The fermentation process of yoghurt involves Lactobacillus bulgaricus and Streptococcus thermophilus as lactic acid-producing microorganisms. The fermentation temperature is a crucial factor affecting the quality of yoghurt; therefore, an accurate temperature control system is required, one of which can be achieved through the implementation of the fuzzy control method. The addition of sweet corn extract is also applied to enhance the flavor of the product. This study aims to analyze the effect of implementing a fuzzy Neo-based temperature control system and the variation of sweet corn extract concentration on the physicochemical properties of yoghurt. The fermentation process was carried out at temperatures of 39.97 °C and 44.99 °C with the addition of 30% and 60% sweet corn extract. The results showed that the best treatment was obtained from yoghurt produced with fuzzy-based temperature control at 44.99 °C and 30% sweet corn extract addition (F-30%-44.99 °C), which exhibited a pH value of 4.3, total soluble solids of 11.5°Brix, viscosity of 124 m.Ps, and lactic acid content of 0.7905%.